Endogenous triglyceride-rich lipoproteins accumulate in rat plasma when competing with a chylomicron-like triglyceride emulsion for a common lipolytic pathway. - Karpe, F; Hultin, M (1995)
The rat liver secretes very low density lipoproteins (VLDL) containing either apoB-100 or apoB-48. After oral fat intake, chylomicrons containing apoB-48 and endogenously synthesized VLDL are mixed in the blood and the triglyceride clearance from these triglyceride-rich lipoprotein species compete for the same lipolytic pathway, i.e., lipoprotein lipase. A situation mimicking alimentary lipemia was induced by a short-term intravenous primed infusion of a chylomicron-like triglyceride emulsion to fed and fasted rats. The plasma concentration of apoB-100 and apoB-48 was monitored in triglyceride-rich lipoprotein subfractions after separation with density gradient ultracentrifugation by analytical SDS-PAGE. The net liver secretory output of VLDL was quantified by lipolytic blockade induced by Triton WR 1339. The chylomicron-like triglyceride emulsion induced a linear increase of large VLDL (Sf 60-400 subfraction containing both apoB-100 and apoB-48), almost to the same extent as that induced by Triton. The clearance of postprandial triglyceride-rich lipoproteins and both lipolysis and clearance of intravenously injected labeled rat chylomicrons was efficiently inhibited by the emulsion but not so complete as for fasting VLDL. The linearity of the VLDL increase and the very early response in the Intralipid-treated rats suggest that enhanced synthesis of VLDL is not a major cause for the accumulation. Rather, the present data indicate that a high plasma concentration of a chylomicron-like triglyceride emulsion competes efficiently with liver-derived VLDL for the same lipolytic pathway, which leads to accumulation in plasma of endogenous VLDL in the postprandial state.